Importance of shoulder girdle and finger flexor muscle endurance in advanced male climbers - Draga, Paweł; Rokowski, Robert; Sutor, Alexander; Pandurevic, Dominik; Michailov, Michail Lubomirov (Frontiers in Sports and Active Living, 2024)
(1)This study aimed to: (a) assess the relationships between climbing performance and finger and shoulder girdle muscle endurance; and (b) provide evidence on the validity of the specialized exercise tests used for the purpose. (2)Materials and Methods: 28 male sport climbers (climbing ability 23 ± 2.43 IRCRA scale) performed four tests for muscle failure, including two-finger hang tests (using 2.5 and 4 cm holds) and two variants of pull-up exercises (classical pull-ups and a combination of dynamic and isometric actions – the so-called Edlinger). Climbing performance and test results were subjected to correlation, taxonomic analysis, and regression analysis. (3)Results: The correlations between the results from all tests and climbing performance were notably strong (r between 0.54 and 0.61) and statistically significant (p < 0.05). The taxonomic analysis indicated that the two variants of each test type reflect two different latent variables 2.5 cm and 4 cm finger hang durations were highly correlated (r = 0.76, p < 0.01). A similar correlation was found between the results from the pull-up tests (r = 0.72, p < 0.01). Thus, the finger hang and pull-up test results were determined to a high extent (43% and 49%, respectively) by factors that cannot be assessed when only one test of each type is used. The regression model of the two-finger tests allowed individual endurance profiles to be assessed. (4)Conclusions: The muscular endurance of the elbow flexors and shoulder girdle muscles predicts climbing performance within the specific sport level studied to a comparable degree as finger flexor endurance.The use of two variants of a test intended to assess one physical ability provided important details on a climber’s fitness.